1991
DOI: 10.2118/20194-pa
|View full text |Cite
|
Sign up to set email alerts
|

Change in Apparent Viscosity off CO2 Foam With Rock Permeability

Abstract: Summary This paper summarizes new and previous high-pressure experiments measuringthe mobility of CO2 foam in porous rock, including both sandstones andcarbonates, with permeabilities ranging from less than 1 md to hundreds ofmillidarcies. Foam mobility is defined here as the ratio of the combined flowrate per unit superficial area to the pressure drop required for simultaneousflow of dense CO2 and brine/surfactant through the sample and can be expressedin units of millidarcies per centipoise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 17 publications
2
56
0
Order By: Relevance
“…Foams are employed for mobility control in situations where polymers, gas or water alternating gas injection schemes are not feasible due to unfavorable conditions, such as low permeability, formation heterogeneity and high temperature-high salinity conditions beyond the polymer stability window. Foam injection has advantages over simple gas injection, and it is demonstrated that the use of foam can mitigate gas channeling, improve apparent gas density and hinder gas escape through high-permeability zones to achieve good oil recovery (Julio and Emanuel 1989;Huh and Rossen 2008;Lee et al 1991;Schramm and Wassmuth 1994). Foams are reviewed in detail in Sect.…”
Section: Foams Wettability Alteration and Lowering Of Interfacial Tementioning
confidence: 99%
“…Foams are employed for mobility control in situations where polymers, gas or water alternating gas injection schemes are not feasible due to unfavorable conditions, such as low permeability, formation heterogeneity and high temperature-high salinity conditions beyond the polymer stability window. Foam injection has advantages over simple gas injection, and it is demonstrated that the use of foam can mitigate gas channeling, improve apparent gas density and hinder gas escape through high-permeability zones to achieve good oil recovery (Julio and Emanuel 1989;Huh and Rossen 2008;Lee et al 1991;Schramm and Wassmuth 1994). Foams are reviewed in detail in Sect.…”
Section: Foams Wettability Alteration and Lowering Of Interfacial Tementioning
confidence: 99%
“…Pressure and temperature should not cause much difference to the flow behavior if CO 2 is in a supercritical state. But they do affect interfacial tension to some extent (Lee and Heller, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…To check the CO 2 flow rates from the Ruska pump, a short length of capillary tube upstream of the foam generator is used to measure CO 2 flow rate (Lee and Heller, 1991 The second surfactant used was Chevron Chaser CD 1045 (Tsau and Heller, 1992;Chou, 1991). CD 1045 was provided by Chaser International.…”
Section: New Experimental Study Experimental Approachmentioning
confidence: 99%
“…The IFT and foam stability apparatus used in this study was designed for testing surfactant properties at high pressure, thus allowing the evaluation of these solutions for reservoir use. An earlier stability apparatus 53,54 was modified with the following additions:…”
Section: Executive Summarymentioning
confidence: 99%
“…More details on a similar system can be found in earlier publications. [53][54][55][56] Like other types of colloidal dispersions, foams are not thermodynamically stable, Eventually they collapse, but it is possible to make surfactant-stabilized, static bubbles and films that endure for months or even years under suitable conditions. Though foams are not thermodynamically stable, they can exhibit kinetic stability, which is defined here as the CO 2 foam kinetic stability.…”
Section: Executive Summarymentioning
confidence: 99%